Effects of TORC1 Inhibition during the Early and Established Phases of Polycystic Kidney Disease - Ta, Michelle H. T. (PLoS One, 2016)
The disease-modifying effects of target of rapamycin complex 1 (TORC1) inhibitors during different stages of polycystic kidney disease (PKD) are not well defined. In this study, male Lewis Polycystic Kidney Disease (LPK) rats (a genetic ortholog of human NPHP9, phenotypically characterised by diffuse distal nephron cystic growth) and Lewis controls received either vehicle (V) or sirolimus (S, 0.2 mg/kg by intraperitoneal injection 5 days per week) during the early (postnatal weeks 3 to 10) or late stages of disease (weeks 10 to 20). In early-stage disease, sirolimus reduced kidney enlargement (by 63%), slowed the rate of increase in total kidney volume (TKV) in serial MRI by 78.2% (LPK+V: 132.3±59.7 vs. LPK+S: 28.8±12.0% per week) but only partly reduced the percentage renal cyst area (by 19%) and did not affect the decline in endogenous creatinine clearance (CrCl) in LPK rats. In late-stage disease, sirolimus reduced kidney enlargement (by 22%) and the rate of increase in TKV by 71.8% (LPK+V: 13.1±6.6 vs. LPK+S: 3.7±3.7% per week) but the percentage renal cyst area was unaltered, and the CrCl only marginally better. Sirolimus reduced renal TORC1 activation but not TORC2, NF-κB DNA binding activity, CCL2 or TNFα expression, and abnormalities in cilia ultrastructure, hypertension and cardiac disease were also not improved. Thus, the relative treatment efficacy of TORC1 inhibition on kidney enlargement was consistent at all disease stages, but the absolute effect was determined by the timing of drug initiation. Furthermore, cystic microarchitecture, renal function and cardiac disease remain abnormal with TORC1 inhibition, indicating that additional approaches to normalise cellular dedifferentiation, inflammation and hypertension are required to completely arrest the progression of PKDs.